2017
DOI: 10.1039/c6cc09387f
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic ATRA reaction promoted by iodo-Bodipy and sodium ascorbate

Abstract: Using ascorbate as a sacrificial reductant, iodo-Bodipy dye 1b is able to promote the ATRA reaction between bromoderivatives and alkenes. This finding expands the possibility of using Bodipy dyes to promote photocatalytic reactions in efficient ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 33 publications
4
51
0
1
Order By: Relevance
“…In this case, only one example using bromoacetonitrile was reported . A very recent photoorganocatalytic example, demonstrating a single example with bromoacetonitrile was also reported by Cozzi and co‐workers . Also, two methods were developed for the addition of bromoacetonitrile to styrene derivatives under photoredox catalysis (Scheme C) .…”
Section: Introductionsupporting
confidence: 87%
“…In this case, only one example using bromoacetonitrile was reported . A very recent photoorganocatalytic example, demonstrating a single example with bromoacetonitrile was also reported by Cozzi and co‐workers . Also, two methods were developed for the addition of bromoacetonitrile to styrene derivatives under photoredox catalysis (Scheme C) .…”
Section: Introductionsupporting
confidence: 87%
“…Based on thorough investigation of the polymerization process, we greatly enhanced the polymerization efficiency and successfully outlined the full mechanism of O‐START polymerization. During our research process, Gualandi and co‐workers reported photomediated atom transfer radical addition (ATRA) catalyzed by iodo‐Bodipy/ l (+)‐ascorbic acid sodium salt, which further validated the mechanism we proposed. As our polymerization was a free radical mechanism and high tolerant to functional groups, various polar or ionic groups could be easily inserted into the polymerization chain through monomer structure design, not restricted to those presented here ( Scheme b).…”
Section: Methodssupporting
confidence: 73%
“…and the corresponding iminium, thereby self‐propagating the reaction in a radical chain fashion (Scheme ) . Control experiments in aerated solutions did not show any significant conversion to acetophenone or other dehalogenated species, suggesting that the presence of O 2 (both at the triplet ground state and at its singlet excited state) is detrimental to the evolution of the radical mechanism as depicted in Scheme . Furthermore, we expect that, given their slow deactivation in deaerated solvents (around 50 μs in C 6 H 6 for PXXMI and PXXDI ), the triplet excited states of imide‐derivatives could also contribute to some extent to trigger the same transformation via an ET process.…”
Section: Resultsmentioning
confidence: 95%